Improved enzyme thermal stability, loading and bioavailability using alginate encapsulation. (April 2023) - Weng, Yilun; Ranaweera, Supun; Zou, Da; Cameron, Anna P.; Chen, Xiaojing; Song, Hao; Zhao, Chun-Xia
Abstract: Enzymes are important biocatalysts for industries. However, many enzymes are sensitive to high temperatures involved in common industrial processes which could decrease or even completely destroy the enzyme activity. To address this issue, many approaches have been developed to improve enzyme thermal stability. Our previous study has demonstrated that enzyme encapsulation using alginate microparticles is effective in improving enzyme thermal stability. However, it remains a challenge to improve not only enzyme thermal stability, but also enzyme loading as well as bioavailability. Bioavailability is critical for encapsulated enzymes, especially in food and feed industries when enzymes are used as food additives. In this study, we optimized the overall enzyme encapsulation efficiency using a three-fluid nozzle spray drying process, and achieved a high enzyme loading of 48 wt% with a high enzyme thermal stability. The encapsulated enzyme showed much less conformational structural changes when subjected to heat treatment, compared with native enzymes. Furthermore, an in vivo animal trial of the encapsulated enzyme demonstrated an excellent bioavailability. Compared to free enzyme, the encapsulated enzyme was able to promote the absorption of phosphorus and calcium, further enhancing the animal overall performance. Graphical abstract: Image 1 Highlights: The enzyme thermal stability was increased almost four folds (from 20% to 79%) using alginate encapsulation. Enzyme loading capacity was improved significantly (up to 48 wt%). Safe materials with zero toxicities were used for the whole manufacturing process. Good bioavailability of the encapsulated enzyme was confirmed by animal trials. The encapsulated enzyme has great potential for applications in food and animal feed industries.